FUNGSI SOSIAL PANTANG LARANG MASYARAKAT BATAK MANDAILING SIMANGAMBAT PADANG LAWAS UTARA - Siti Lanna Hasibuan; M. Nur Mustafa; Elmustian ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study entitled Taboos Community Batak Mandailing Simangambat Padang Lawas. This study aims to find Taboos Community Batak Mandailing Simangambat Padang Lawas. The data in this study is the social function of taboo in the form of a social function taboo performers liver, social taboos bearing, and social functions taboo spiritual perfection. This type of research is qualitative descriptive. The object of this study is taboo. The data source is the object of this study is taboo society Batak Mandailing Simangambat Padang Lawas. To get the data the authors conducted a field survey techniques, interview techniques, recording techniques, and techniques confirmation record taboos of society Italiana Simangambat Padang Lawas. The results of this study are as follows. (1) taboos as an entertainer heart, (2) taboo bearing, (3) the taboo of spiritual perfection. Taboos are more dominant in society Italiana Simangambat Padang Lawas is taboo worthwhile.Key Words: Taboos, Batak Mandailing